Helpful Enterprise Architecture Elements for Organizational Networks - Maris, Arjen; Ravesteijn, Pascal; Hoppenbrouwers, Stijn; van Hillegersberg, Jos (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Healthcare organizations increasingly collaborate within networks of private and public partners. To do so, data is recorded, stored and exchanged with help of a complex landscape of information systems (IS). While IS landscapes could boost digital innovation, they also generate significant administrative burdens. Enterprise Architecture (EA) supports organizations in managing IS landscapes. However, current EA practices do not fit well on the dynamics of networks, and research on EA for networks is scarce. Therefor the research objective is to determine what EA elements help to manage an IS landscape within healthcare organizations that collaborate in a network structure. Three group sessions were conducted using a collaboration engineering approach to refine network characteristics and usefull EA elements. The findings indicate that 'network motive' and 'network governance mechanisms' are the most important network characteristics, while 'EA goals' and 'EA processes' are the most helpful for network architecture (EA for a network).